Intraocular Pressure Changes of Rhegmatogenous Retinal Detachment Patients Following Pars Plana Vitrectomy in Tertiary Hospital - Wardani, Sabrina Indri; Virgana, Rova (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2024)
Introduction: Rhegmatogenous retinal detachment (RRD) is one of the leading causes of vision loss worldwide. Retinal reattachment is the main target of RRD management. Pars plana vitrectomy (PPV) is one of the surgical approaches to reattach the retina by removing the vitreous gel and replacing it with tamponades. Several tamponades used in PPV may cause an alteration of intraocular pressure (IOP). Purpose: To report the IOP changes of RRD patients who underwent pars plana vitrectomy surgery Methods: A descriptive retrospective study was conducted on all RRD patients who underwent primary PPV with all tamponades at the National Eye Center, Cicendo Eye Hospital. This study has evaluated and observed the range of IOP across all the follow-up timelines post-surgery based on the endo tamponade used for the patients. Result: A total of 90 patients received intravitreal tamponade. The median IOP at baseline was 12 (4-21) mmHg. Secondary glaucoma mostly occurred in 1st and 3rd months post-PPV, 37.78% and 36.67% respectively. 80% of patients who received silicon oil 1300 centistoke experienced IOP elevation which occurred highly during 1-week and 1-month post PPV. 2.2% of patients underwent glaucoma filtering surgery to further control the IOP elevation. Conclusion: PPV procedure with several types of tamponades as vitreous substitution is one of the common approaches for patients with RRD. IOP elevation has been observed as one complication of PPV. Multiple factors may be attributable to IOP alteration. Monitoring of IOP before and after the surgery is mandatory to prevent secondary complications